2009
DOI: 10.1063/1.3271028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity of polymer composites filled with three-dimensional brushlike AlN nanowhiskers

Abstract: The thermal conductivity of polymer composites was improved by loading three-dimensional (3D) brushlike AlN nanowhiskers fillers synthesized by simple combustion method. Through filling 47 vol % of the synthesized AlN nanowhiskers, the thermal conductivity of the composite was significantly increased to 4.2 W m−1 K−1, which was 2.3 times higher than that of the composite filled with the same content of commercial AlN equiaxed particles. According to Agari model analysis and microstructure observation, the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…In order to enhance the thermal conductivity, many kinds of materials such as metals, ceramics, and thermally conducting fillers have been applied. However, their disadvantages, including poor corrosion resistance, heavier weight, and high micro-filler loading, have suggested a need for another kind of material [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the thermal conductivity, many kinds of materials such as metals, ceramics, and thermally conducting fillers have been applied. However, their disadvantages, including poor corrosion resistance, heavier weight, and high micro-filler loading, have suggested a need for another kind of material [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thermally conductive polymers arouse more attention due to their corrosion resistance, lightweight and good flexible properties [9]. Epoxy resin is one of typical polymer matrices, and SiC, Al 2 O 3 , BN have been widely adopted as thermally conducting fillers to cope with thermal management issues [10,11]. However, in order to achieve the satisfied thermal conductivity (1$5 W m À1 K À1 ), the loading fraction of the filler always exceeds 60 vol%, which leads to a high bulk density and poor mechanical properties [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various parameters have been studied to enhance the thermal performance of the polymer based thermally conductive composite materials including different types of filler materials such as oxides [4][5][6], nitrides [7][8][9][10][11][12][13], carbides [14,15] and carbon material [3,[16][17][18], different types of matrix materials such as PE [1,19], PS (Polystyrene) [9,20], PP [2,3], and epoxy [5,10,13,15,21,22], size of the fillers [13,19], aspect ratio of the fillers [21]. It was reported that a boron nitride (BN)-filled polybenzoxazine composite with its maximum filler loading of 78.5% by volume achieved a significant high thermal conductivity of 32.5 W/(m K) [7].…”
Section: Introductionmentioning
confidence: 99%